[OP.6B.05] ALDOSTERONE PROMOTES MYOCARDIAL EXTRA-CELLULAR MATRIX REMODELING QUANTIFIED BY MAGNETIC RESONANCE IMAGING IN HUMANS INDEPENDENT FROM THE EFFET OF BLOOD PRESSURE. (September 2017) - Redheuil, A.; Blanchard, A.; Raissuni, Z.; Roux, C.; Soulat, G.; Azarine, A.; Chatellier, G.; Amar, L.; Plouin, P.; Boutouyrie, P.; Azizi, M.; Kachenoura, N.; et al.
Abstract : Objective: Aldosterone is central to homeostasis, blood and extracellular fluid regulation and promotes interstitial myocardial fibrosis directly and through secondary hypertension. Magnetic resonance imaging (MRI) is a sensitive method to non invasively quantify extra cellular matrix changes in vivo using T1 tissue relaxation properties. Our aim was to characterize aldosterone-related intra and extracellular myocardial changes independent from hypertension in relation to ventricular remodeling in humans. Figure. No caption available. Design and method: Twenty consecutive patients with primary hyperaldosteronism (PHA) were matched with 20 patients with essential hypertension (HTN) and 20 patients with Bartter-Gitelman syndrome (BG) matched with 20 healthy controls. Total, intra- and extracellular myocardial mass indexed to body surface area were calculated by MRI in 80 individuals using a double case-controlled design to study the respective effects of aldosterone and blood pressure and compared across groups. Results: Compared to healthy controls, BG patients with hyperaldosteronism but low volemia (cardiac preload) and normal blood pressure showed decreased intracellular mass (36 ± 7.5 vs. 42 ± 8.5 g/m 2, p = 0.029) and similar extracellular mass leading to lower total myocardial mass (52 ± 6.6 vs. 58 ± 9.1 g/m 2, p = 0.029). Compared to healthy controls, HTN patients without hyperaldosteronism but increased cardiac afterload showed increased intracellular mass (49 ± 7.9 vs. 42 ± 8.5 g/m 2, p = 0.03) and similar extracellular mass leading to higher total myocardial mass (64 ± 8.7 vs. 58 ± 9.1 g/m 2, p = 0.029). However, PHA patients with hyperaldosteronism associated with higher blood pressure levels demonstrated markedly increased total mass (77 ± 18 vs. 58 ± 9.1 g/m 2, p < 0.001) secondary to an increase in both intra (56 ± 16 vs. 42 ± 8.5 g/m 2, p = 0.001) and extracellular mass (23 ± 7.6 vs.15.5 ± 5.3 g/m 2, p = 0.001) compared to healthy controls and differed from the HTN patients by preferential increase of the extracellular compartment (23 ± 7.6 vs. 15 ± 4.1 g/m 2, p = 0.007). Conclusions: Differential effects of aldosterone and blood pressure on intra and extracellular components of the myocardium could be quantified non invasively in humans using MRI. Hyperaldosteronism associated with hypertension leads primarily to myocardial extracellular matrix expansion whereas isolated hypertension leads exclusively to increased intracellular mass.